2023
DOI: 10.1001/jamanetworkopen.2023.41096
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Candidates for Hepatocellular Carcinoma Liver Transplant After 6-Month Wait Policy Change

Behnam Saberi,
Ahmet Gurakar,
Hani Tamim
et al.

Abstract: ImportanceRacial disparities in liver transplant (LT) for hepatocellular carcinoma (HCC) may be associated with unequal access to life-saving treatment.ObjectiveTo quantify racial disparities in LT for HCC and mortality after LT, adjusting for demographic, clinical, and socioeconomic factors.Design, Setting, and ParticipantsThis cohort study was a retrospective analysis of United Network Organ Sharing/Organ Procurement Transplant Network (OPTN) data from 2003 to 2021. Participants were adult patients with HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…20,21 The authors hypothesized that this was due to Asian patients having a higher risk of suffering from simultaneous HBV infections, having lower MELD scores and more compensated status of liver disease. 22 In our study, of all 253 patients listed with positive HBV serology in the timeframe of the study, 65% were Asian. In addition, nearly 53% of all waitlisted Asian HCC LT candidates had positive HBV serology, which raises further suspicion that a comorbid HBV infection may have contributed to the finding.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…20,21 The authors hypothesized that this was due to Asian patients having a higher risk of suffering from simultaneous HBV infections, having lower MELD scores and more compensated status of liver disease. 22 In our study, of all 253 patients listed with positive HBV serology in the timeframe of the study, 65% were Asian. In addition, nearly 53% of all waitlisted Asian HCC LT candidates had positive HBV serology, which raises further suspicion that a comorbid HBV infection may have contributed to the finding.…”
Section: Discussionmentioning
confidence: 63%
“…reported that Asian LT candidates with HCC had the lowest waitlist removal rates in more contemporary eras. The authors hypothesized that this was due to Asian patients having a higher risk of suffering from simultaneous HBV infections, having lower MELD scores and more compensated status of liver disease 22 . In our study, of all 253 patients listed with positive HBV serology in the timeframe of the study, 65% were Asian.…”
Section: Discussionmentioning
confidence: 70%